Exploring Student Engagement in Online Learning - Pratiwi, Hafizah; Priyana, Joko (Universitas Negeri Malang, 2022)
This survey study aimed to capture the actual student engagement in online learning, including the intensity of engagement, the barriers that prevent the students from engaging, and the efforts to stay engaged during online learning. It determined the students’ and English teachers’ perspectives to identify the differences in engagement variables among them. There were 424 participants consisting of students and English teachers from 2 Senior High Schools, 1 Vocational High School, and 2 Junior High Schools in South Sumatera, Indonesia. The online questionnaire was distributed through Google Forms and divided into three parts. The questionnaire items were adopted from Online Student Engagement Scale (OSE) to measure the intensity of engagement and Microsystem Factors Influence Student Engagement Scale to investigate the students’ barriers and efforts in engaging in online learning. Further, all the garnered data were computed through SPSS 25.0, facilitating an easier data presentation. The results of this study unveil the moderate intensity of student engagement in online learning, low barriers, and high efforts to stay engaged during online learning from both students and English teachers' perspectives. Addition-ally, these results are expected to be used as the basis of reflection and evaluation of the online learning program in Indonesia